POLRI DI ERA DEMOKRASI : Dinamika Pemikiran Internal - Yanuarti, Sri (Jurnal Penelitian Politik, 2025)
Police reform is an integralpart ofholistic security sector reform SSR which aims to create goodgovernance in the security sector and to create a secure and orderly environment Thus in accordance with the principles of democracy police reform should have been directed to build a civilian policing character based on democratic norms openness and accountability Although police reform already been done since more than a decade ago its implementation has not been optimal Thepresence ofpolice as an institution and its members still have a negative image in the eyes ofpeople because ofthe actions ofcertain person ofpolice personnel The study is to describe 1 How does the present shift ofIndonesian police from the era ofauthoritarianism to era of democracy 2 what factors that encourage and inhibit the process ofpolice reform what kind ofconstraints that itface as well as the impact ofthe constraints 3 How do internal dynamics which occurs in the thought ofpolice reform itself